Adhesion forces between macrophages and cancer cells promote early tumor development - Jovan Nikolic; Joseph Ackermann; Ines Marin; Sarah Taheraly; Morgane Mabire; François-Xavier Gobert; Mathieu Maurin; Apolline de Testas de Folmont; Ouardia Aït-Mohamed; Edison Gerena; Sophie Goyard; Jérémy Mesple; et al. (Proceedings of the National Academy of Sciences, 2026)
Biochemical mechanisms of macrophage-driven tumor promotion are well documented, but the contribution of physical forces to early tumor development remains poorly understood. Here, we combine experimental analyses with physical modeling to investigate these forces in Kras G12D p53 −/− (KP) lung tumor spheroids grown in 3D. Real-time microscopy showed that tissue-resident macrophages, but not monocytes, promote early tumor growth. Using quantitative measurements, we built a physical model that recapitulates cancer cell proliferation dynamics and macrophage–tumor interactions. KP tumor cells grown alone formed a single aggregate that contracted over time due to nutrient limitation, whereas macrophages induced the formation of multiple aggregates that grew, fused, and expanded nutrient access, thereby increasing proliferation. Similar macrophage-driven growth was observed when alveolar or bone-marrow–derived macrophages were cocultured with KP or pancreatic carcinoma cells. The model predicted a redistribution of macrophages toward the periphery of aggregates, a pattern confirmed in vitro and previously observed in vivo. It also identified adhesion forces between tumor cells and macrophages as a key driver of spheroid nucleation and growth. Among candidate integrins, CD11c was highly expressed by alveolar macrophages; CD11c blockade reduced adhesion forces, prevented macrophage-driven spheroid nucleation, and impaired tumor growth. Bone-marrow-derived macrophages required simultaneous CD11b and CD11c blockade for similar effects. Finally, CD11c inhibition in RAG-Knock Out (KO) mice reduced tumor survival probability and slowed the growth of ear-implanted tumors, indicating that CD11c-dependent interactions support tumor establishment beyond the lung. Together, these findings uncover a critical physical mechanism through which macrophages promote early tumor progression.